Pengajaran Agama Berbasis Mobile Learning - Anam, Saeful; Rihadatu `Aisy, Nanda Mutiara (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
The research aims to determine the increase and comparison of students ` learning outcomes through the use of mobile learning-based recitation methods. We know that mobile learning is an online medium that can be used all the time. This method of study used quasi for using test paired sample t-test. The results showed that there was influence of learning methods based on mobile learning recitation of the student learning outcomes where the value of Thitung 8.913 is greater than the level of significance 5% (2.778) and 1% (3.435), the value of probability 0.000 < 0.05, of these values, show that the influence of the learning method of a mobile learning Recitation is based on the